Trade-Off Spasial antara Ekspansi Pertanian Jagung dan Kualitas Lingkungan: Integrasi Analisis Deforestasi menggunakan Citra Sentinel-2A dan Indeks Kualitas Lingkungan Hidup di Kabupaten Dompu, Indonesia - Nurhidayah; Nurhayati; Sukuryadi; Joni Safaat Adiansyah (Mataram University, 2026)
The expansion of corn cultivation in Dompu Regency, West Nusa Tenggara, has the potential to generate significant economic growth but simultaneously places ecological pressure on protected forest areas. This study examines the spatial trade-off between agricultural expansion, particularly corn, and environmental quality in Dompu Regency by integrating Sentinel-2A image-based deforestation analysis (2019–2026) with Environmental Quality Index (IKLH) data from 2021–2025. Analysis results show that the area of dryland agriculture increased drastically from 7,602.02 ha to 92,115.24 ha, while primary forest cover decreased by 6,335.12 ha and shrub/scrub cover decreased by 49,131.65 ha. Deforestation reached 73,729.50 ha, and forest degradation covered 14,926.75 ha. On the other hand, corn production in Dompu Regency increased significantly from 302,117 tons (2020) to 629,011 tons (2022), although it experienced fluctuations in subsequent years. The IKLH analysis shows fluctuating values with an improving trend by 2025 (76.48), yet the components of the Water Quality Index (IKA) and Land Cover Quality Index (IKL) remain in the poor category. The identification of spatial trade-off zones—Critical Transition Zones in the sub-districts of Pekat, Kempo, and Woja; Ecologically Vulnerable Zones in the northern part; and Production Stabilization Zones in the southern part—provides a scientific basis for recalibrating spatial planning policies that integrate ecological boundaries into agricultural land-use planning.